EKSISTENSI BURUH MIGRAN PEREMPUAN DAN GAMBARAN KEMISKINAN KABUPATEN PATI - Aeni, Nurul (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah (BAPPERIDA) Kabupaten Pati, 2017)
ENGLISHIndonesian migrant workers are dominated by women. It is an evidence of women participation in local development due to the remittance. This research aimed to describe the distribution of woman migrant workers in Pati District and to compare the poverty level between the subdistricts whose high concentration of woman migrant workers and their counterparts. It used qualitative research design with secondary data that were obtained from Employement and Transmigration Service as well ase Local Development Agency of Pati District. The result of reserach were: (1) The growth of woman migrant workers in Pati District during 2015-2016 was 24%. They mostly works in domestic sector with the main destination country is Taiwan. The highest consentration of woman migrant workers was Sukolilo Subdistrict and the lowest’s was Batangan Subdistrict. (2) Poverty is probably one of the international migration’s triggers. The subdistricts with high concentration of woman migrant workes tend to have higher percentage of poor families compare to their counterparts. INDONESIABuruh Migran Indonesia (BMI) dari Kabupaten Pati didominasi oleh perempuan. Hal tersebut menjadi bukti peran serta perempuan dalam pembangunan daerah berkaitan dengan pengiriman remitan. Tujuan penelitian adalah menggambarkan persebaran buruh migran perempuan di Kabupaten Pati dan membandingkan kondisi kemiskinan di kecamatan dengan jumlah buruh migran perempuan terbanyak dan tersedikit. Penelitian menggunakan desain kuantitatif dengan data sekunder yang didapatkan dari Disnakertrans, Bappeda Kabupaten Pati serta referensi lain yang relevan. Pengolahan data menggunakan analisis deskriptif. Hasil penelitian menunjukkan: (1)Pertumbuhan buruh migran perempuan di Kabupate Pati periode 2015-2016 adalah sekitar 24%. Sebagian besar buruh migran tersebut bekerja di sektor domestik dengan destinasi utama Taiwan. Konsentrasi buruh migran tertinggi berada di Kecamatan Sukolilo dan terendah di Kecamatan Batangan. (2) kemiskinan diindikasikan menjadi salah satu faktor yang melandasi keputusan menjadi buruh migran. Bukti akan hal tersebut adalah kecamatan dengan jumlah buruh migran perempuan banyak memiliki persentase keluarga miskin yang lebih tinggi.